Biomaterials-Induced Stem Cells Specific Differentiation Into Intervertebral Disc Lineage Cells - Peng, Yizhong; Huang, Donghua; Liu, Sheng; Li, Jinye; Qing, Xiangcheng; Shao, Zengwu (Frontiers in Bioengineering and Biotechnology, 2020)
Stem cell therapy, which promotes stem cells differentiation towards specialized cell types, increases the resident population and production of extracellular matrix, and can be used to achieve intervertebral disc (IVD) repair, has drawn great attention for the development of IVD-regenerating materials. Many materials that have been reported in IVD repair have the ability to promote stem cells differentiation. However, due to the limitations of mechanical properties, immunogenicity and uncontrollable deviations in the induction of stem cells differentiation, there are few materials that can currently be translated into clinical applications. In addition to the favourable mechanical properties and biocompatibility of IVD materials, maintaining stem cells activity in the local niche and increasing the ability of stem cells to differentiate into nucleus pulposus (NP) and annulus fibrosus (AF) cells are the basis for promoting the application of IVD-regenerating materials in clinical practice. The purpose of this review is to summarize IVD-regenerating materials that focus on stem cells strategies, analyse the properties of these materials that affect the differentiation of stem cells into IVD-like cells, and then present the limitations of currently used disc materials in the field of stem cell therapy and future research perspectives.